Planning and The People A Study of Public Participation in Planning in Uttar Pradesh - Planning Commission (Planning Commission, 1961)
Simultaneous with the achievement of political freedom, India has taken up the task of economic and social uplift through democratic planning. The Planning Commission has rightly appraised the need for securing popular support and co-operation at every stage of this vital task. It is widely admitted that India has not the faintest chance of developing unless the people are prepared to undertake individually and collectively to work hard and in a disciplined manner.
Planning Commission Government of India
Planning Commission Government of India